Recurrent connections between Amazon and Atlantic forests shaped diversity in Caatinga four-eyed frogs - Thomé, Maria Tereza C. [UNESP]; Sequeira, Fernando; Brusquetti, Francisco [UNESP]; Carstens, Bryan; Haddad, Célio F. B. [UNESP]; Rodrigues, Miguel Trefaut; Alexandrino, João (Wiley, 2016)
Aim: The Caatinga is a widespread but poorly known biome in South America. Its historical stability is controversial and different types of evidence provide support to contrasting hypotheses. We investigate how past biome dynamics may have caused diversification in the endemic four-eyed frog genus Pleurodema. Location: Caatinga biome. Methods: We sampled 353 individuals of Pleurodema alium and Pleurodema diplolister from 60 localities and genotyped them at 12 (P. alium) or 20 (P. diplolister) microsatellite loci. We sequenced a mitochondrial fragment for a subset (199) of the samples. After exploratory analyses to infer genetic structure between and within species, we designed seven biogeographical scenarios based on the literature on species distributions, palaeomodels and geological palaeoindicators. We tested these hypotheses by calculating the posterior probability of models using multilocus approximate Bayesian computation (ABC). Results: Both markers recovered well-defined interspecific limits with restricted introgression, but population structure within P. diplolister is subtle and affected by isolation by distance. Model selection using ABC supported two scenarios of diversification that included recent demographic growth. Genetic breaks at intra- and interspecific levels were geographically coincident, and correlated with past forest invasions reported in the literature. Main conclusions: Our data support the idea that past expansions of the Amazon and Atlantic forests over the current Caatinga distribution shaped the genetic structure in endemic four-eyed frogs at more than one level by promoting intermittent vicariance. Additional support comes from the distribution patterns of forest and Caatinga taxa. Variation among groups suggests differential organismal responses to past habitat shifts, probably mediated by specific natural-history traits. This paper provides the first direct evidence that taxa endemic to the Caatinga were affected by past forest interactions.
Keywords: ABC; Chapada Diamantina; Forest corridor; Microsatellites; Past habitat shifts; Phylogeography; Pleurodema; Semi-arid biome